Intelligent robots in the Directory: Board of Directors of commercial companies - Pérez Carrillo, Elena F. (2024)
This paper discusses some of the obstacles to incorporating intelligent robots into corporate governance, primarily through the board of directors (BoD). And it offers ideas on how the transition could take place, overcoming the most problematic aspects of AI.